Діалог як інформаційна модель (на матеріалах традиційної культури) - Темченко А. (Народна творчість та етнографія, 2005)
This article is a description of the possible ways that the humans can code the information and the dialog as one of the possibilities for coding and passing information. Author is looking at the dialog as a metaphoric polycemantic philosophical category not just a pragmatical way of coding and passing information. Special attention author is paying to the ritual dialogs and way of coding of the mythological information.